Revisiting the paradox of well-being: the importance of national context - Swift, H. J. (2015)
Objectives. Despite age-related changes or declines in circumstances, health or income, many older people are able to maintain subjective well-being (SWB) in later life. This is known as the paradox of well-being. To date, much research has focused on either individual- (e.g., age, health, and income) or country-level (e.g., national wealth, inequality) differences in SWB. The present research investigates how these levels combine, and whether the paradox of well-being persists across different economic contexts. Method. This research uses the 2008–2009 European Social Survey to test the multilevel hypothesis that economic circumstances, reflected by a country’s Gross Domestic Product (GDP), affect the paradox of well-being, that is, the relationship between age and SWB. Analyses also account for other relevant psychological, individual, and country differences. Possible avenues by which GDP affects SWB are also explored. Results. The multilevel analysis revealed that GDP disproportionally affects the SWB of older people relative to younger people, and that the paradox of well-being is only observed in countries with higher GDP. Discussion. The findings clarify the relationship between age and SWB by demonstrating that the paradox of wellbeing is conditional on the economic context. Implications for individual- and country-level strategies for successful aging are discussed.